2010
DOI: 10.1002/jae.1106
|View full text |Cite
|
Sign up to set email alerts
|

What you match does matter: the effects of data on DSGE estimation

Abstract: This paper explores the effects of using alternative combinations of observables for the estimation of Dynamic Stochastic General Equilibrium (DSGE) models. I find that the estimation of structural parameters describing the Taylor rule and sticky contracts in prices and wages is particularly sensitive to the set of observables. In terms of the model's predictions, the exclusion of some observables may lead to estimated parameters with unexpected outcomes, such as recessions following a positive technology shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 39 publications
(71 reference statements)
3
16
0
Order By: Relevance
“…Guerron-Quintana (2010) documents how parameter estimates of a variant of the SmetsWouters model are affected by the choice of observables used in the Bayesian estimation. Iskrev (2010) and Komunjer and Ng (2011) develop formal conditions for the identifiability of DSGE model parameters based on first and second moments of model variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guerron-Quintana (2010) documents how parameter estimates of a variant of the SmetsWouters model are affected by the choice of observables used in the Bayesian estimation. Iskrev (2010) and Komunjer and Ng (2011) develop formal conditions for the identifiability of DSGE model parameters based on first and second moments of model variables.…”
Section: Introductionmentioning
confidence: 99%
“…Guerron-Quintana (2010) examines how data choice affects parameter identifiability in the Smets-Wouters model by eliminating subsets of the seven macroeconomic time series that are typically used to estimate the Smets-Wouters model.…”
mentioning
confidence: 99%
“…The empirical treatment used in our paper relates to the extensive literature on the estimation of dynamic stochastic general equilibrium models (Fernandez‐Villaverde, Guerron‐Quintana, and Rubio‐Ramirez () and Guerron‐Quintana ()). We are close to Ajello (), who estimates a model with financial frictions in which competitive financial intermediaries transfer resources between entrepreneurs with heterogeneous skills.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the choice of which variables to use in the estimation and the use or not of measurement errors is indeed not a trivial one. Guerron‐Quintana () has shown that, in the estimation of DSGE models by Bayesian methods, posterior distributions may significantly vary across various sets of observables used. In the working paper version of this work, Chang and Fernandez (), we assess the robustness of our results to cases where no measurement errors are used.…”
mentioning
confidence: 99%